The usefulness of intellectual capital information to the financial analysts and fund managers / Norhafizah Che Mat - Che Mat, Norhafizah (2012)
Intellectual capital (IC) has long been recognised as a key corporate value creator in the knowledge-based economy, witnessed by an increase in the disclosure of IC information externally. However, such disclosures fall short of those desired by the users, hence creating an information gap This study explores the importance of IC and the extent of usefulness of IC information to the financial analysts and fund managers, examines how or where IC information is obtained and identifies the challenges faced by them in obtaining IC information. This study employed a postal survey with the aid of a questionnaire. Findings from this study suggest that IC is important to the financial analysts and fund managers in performing companies’ evaluation. As IC is found to be important, the financial analysts and fund managers used IC information to some extent. Relational capital was discovered to be extensively used, followed by structural capital and human capital. The preference towards relational capital is more concerned about cash generating abilities of companies. It was also found that the main sources of IC information were from financial statements and notes to the accounts Lack of public disclosure is the biggest challenge in obtaining IC information. The usefulness of IC information is not dependent to the years of experience or the types of services provided by the users. Overall, this study provides empirical evidence on the usefulness of IC information to the financial analysts and fund managers in carrying out their jobs. It helps to raise awareness amongst companies and regulators in enhancing the disclosures of external IC information Future research may extend the samples size, include other groups of stakeholders, investigate further the use of IC information internally within firms.